ANALISIS PENGARUH ASSETS DAN MANAJEMEN INVENTORY TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG LISTING DI BURSA EFEK JAKARTA (INDONESIA) 2010 - 2012 - Windasari Rachmawati; Vinsensia Retno Widi Wisayang (Universitas Semarang, 2017)
This research aims to study the influence of the values of the quick ratio, asset turnover, return-on - asset and inventory turnover to net income before taxes in the food and beverage industry in the Jakarta Stock Exchange (Indonesia) in 2010-2012. The approach used is a qualitative approach with multiple regression. Based on the analysis described previously, it can take the conclusion of the independent variable asset turnover, return on assets and inventory turnover is partially has positive and significant impact on Ebit or profit. This proves that the previous research studies on assets and inventory management affects earnings before tax (EBIT). From this analysis ATR, ROA and ITO have an influence on Ebit or profit. So that business owners are advised to keep the ATR, ROA, and ITR to always be high to get higher profits.